Formulasi Penyelesaian Tindak Pidana Kekerasan Seksual Dengan Pelaku Anak Yang Berkepastian Hukum - Sieldy Aprilia Utami; Y.A Triana Ohoiwutun; Ainul Azizah (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2024)
Based on the development of theoretical discourse and reform of criminal law in various countries, there is a strong tendency for law enforcers to apply solutions outside the judicial process as a way to resolve problems in the field of criminal law. In general, settlements outside the judicial process are carried out in civil cases. Meanwhile, in the field of criminal law, settlement outside the judicial process is applied to the resolution of cases of children who are in conflict with the law which violates the rules of criminal law which refer to the Child Protection Justice System Law.The crime of sexual violence committed by children is one of the crimes where the case is resolved through a settlement outside the judicial process. In practice, law enforcement officials use different regulations based on each level in the examination process, both at the investigation, prosecution and court examination levels. The differences in written regulations that are used as a legal basis by the Police, Public Prosecutors, or Judges in implementing settlement policies outside the judicial process based on a restorative justice approach through diversion efforts which have implications for legal uncertainty require efforts to reformulate current legal regulations through criminal law policies.